DOI: 10.22215/etd/2015-13389
|View full text |Cite
|
Sign up to set email alerts
|

Selection of DNA Aptamers for Mycotoxins

Abstract: Mycotoxins deoxynivalenol (DON) and patulin (PAT) are toxic fungal metabolites that contaminate food commodities worldwide. They pose health risks for humans and animals, and have a negative impact on the economy. Mycotoxin detection is vital to ensure public safety.Although traditional detection techniques for mycotoxin detection (e.g. LC-MS) have proven to be highly selective and sensitive, simpler, more rapid, and more cost-effective approaches are required. Aptamer-based techniques are a possible solution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 96 publications
(135 reference statements)
0
10
0
Order By: Relevance
“…First, since starting oligonucleotide libraries can typically encompass anywhere from 10 18 to 10 40 possible unique sequences (for libraries containing 30-70 random nucleotides), it is unrealistic to screen every possible sequence in a SELEX experiment, and this will inevitably exclude high-quality aptamer candidates. 6,7 Second, due to the low copy number of each sequence in the starting library, oligonucleotides with desirable binding properties can easily be lost during the early rounds of SELEX. 8,9 Finally, these aptamers can be eliminated if they have low PCR amplification efficiency due to their sequence and/or structure.…”
Section: Introductionmentioning
confidence: 99%
“…First, since starting oligonucleotide libraries can typically encompass anywhere from 10 18 to 10 40 possible unique sequences (for libraries containing 30-70 random nucleotides), it is unrealistic to screen every possible sequence in a SELEX experiment, and this will inevitably exclude high-quality aptamer candidates. 6,7 Second, due to the low copy number of each sequence in the starting library, oligonucleotides with desirable binding properties can easily be lost during the early rounds of SELEX. 8,9 Finally, these aptamers can be eliminated if they have low PCR amplification efficiency due to their sequence and/or structure.…”
Section: Introductionmentioning
confidence: 99%
“…Python scripts are used to create the fuzzer. The fuzzer uses the Pycomm library developed by Ruscito [24] to communicate with the Allen-Bradley ControlLogix PLC of SWaT (specifically, in this experiment, the PLC1 which controls the raw water process). Pycomm is used to emulate realistic attacks against level sensor LIT 101, motorized valve MV 101, and the flow rate indicator F IT 101, by systematically modifying the sensor readings A few preliminary attacks were launched by changing the LIT 101 readings to a constant (randomly chosen) anomalous value (between LL to L or H to HH ) for 30 seconds, restoring it to the actual value, and giving the system time to recover before launching another attack.…”
Section: Traces Generationmentioning
confidence: 99%
“…The difficulty in selecting small molecules may be attributed to the large difference in size between the aptamer and the target, which can cause crowding during selections, thereby decreasing selection efficiency (Ruscito & DeRosa, 2016). Furthermore, binding of the aptamer to a small molecule target does not result in a substantial mass difference, which makes partitioning more challenging.…”
Section: Target Versus Library Immobilizationmentioning
confidence: 99%
“…In fact, in the past two decades, very few changes have been made to the classical small molecule aptamer selection protocol. Reviews on aptamer selection strategies as applied to small molecules can be found in the works of Ruscito and McKeague (McKeague & DeRosa, 2012;Ruscito & DeRosa, 2016).…”
Section: Background Informationmentioning
confidence: 99%
See 1 more Smart Citation